ANALISA KADAR TIMBAL PADA KUKU PEKERJA TAMBAL BAN SEPANJANG JALAN GATOT SUBROTO SECARA SPEKTROFOTOMETER SERAPAN ATOM - Sibuea, Rahul; Aruan, Dyna Grace Romatua; Damanik, Elsarika (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Lead (Pb) is a type of heavy metal that is dangerous and toxic to the human body. Mechanics is one of the professions in the field of motorized vehicle engines, where the possibility of exposure to Pb particles due to pollution or motor vehicle gas emissions with levels much higher than that of other communities is very real. Therefore, Pb exposure will be faster, if it is accompanied by a long duration of exposure. The accumulation of Pb in this study illustrates that the length of work greatly affects the levels of Pb in the hair of workers and the environment which is potentially polluted with Pb has a very high probability of absorbing lead into the workers' bodies. According to WHO (World Health Organization) in 1995 the level of lead levels in the human body was divided into 3 (three) levels, namely, low (<10 ppm), medium (10-25 ppm) or high (>25 ppm) according to the WHO pollution category in 2005. 1995. This study aimed to analyze lead levels in mechanical nails in the Kampung Lalang area. This research was carried out at the UPT Regional Health Laboratory of North Sumatra Province using an Atomic Absorption Spectrophotometer. From the 25 total population, the study took hair samples from 20 (twenty) mechanics. Pb levels in 20 (twenty) mechanical nail samples in the Kampung Lalang area by Atomic Absorption Spectrophotometer in 2021, with a variable duration of work > 10 years (R1) 342 mg/kg including high pollution levels >25 ppm, while samples with a working duration of 5 -10 years (R8) 118.75mg/kg is declared to contain lead with a high pollution category >25ppm, while 3-5 years (R6) 95mg/kg is declared to contain lead with a high pollution category>25ppm and a working period of <3 years ( R7) 13.78 mg/kg enters a moderate pollution level of 10-25ppm. and it is suggested to further researchers to conduct research by taking other samples such as hair or blood to get more accurate results